(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Heavy metals were found to have hazardous impact on man and ecosystem. The efficacy of Rice, Millet and Guinea corn husks was tested for the removal of Cu(II) and Fe(II) ions from aqueous solution. The husks were soaked in the metal ion solutions removed, dried, digested and analyzed by MP-AES. The husks were found to be effective for the removal of the targeted metal ions. The results showed the pattern of removal in the order; RH >GCH > MH and GCH > MH > RH for Cu(II) and Fe(II) respectively. The samples were also analyzed for X-ray Fluorescence (XRF) and Fourier Transform Infrared Spectrometer (FTIR). The XRF result showed oxides like SiO2, MnO, MgO and Fe2O3, etc. with SiO2 having the highest percentage. The results of the FTIR analysis showed the presence of OH, C-H, NH and C=O groups, which indicates tendencies for metal binding. Moreover, the MP-AES results showed that RH had the highest removal capacity of Cu(II) with 95% (76 mg/g), followed by GCH 92.5 % (74 mg/g), and MH has the least removal capacity of 84.5 % (67.6 mg/g). The amount of Fe(II) was found to be high in GCH with 95% (76mg/g) followed by MH, 91.5 % (73.2 mg/g) and RH having the least capacity of 60 % (48 mg/g). Generally, the results indicates that all the agricultural wastes have the capacity to remove the heavy metals significantly. This showed that, the husks can be used to remove heavy metals from wastewater without polluting the environment.